Safe incident reporting in out-of-hours primary care: an exploratory study. Issue 6 (1st November 2016) - Augustyns, Nele; Lesaffer, Caroline; Teughels, Stefan; Philips, Hilde; Remmen, Roy
Abstract : Objectives : The goal of safe incident reporting (SIR) is to recognize avoidable incidents to prevent future harm. Data on the use of SIR in Belgium's out-of-hours primary care (OOHC) services are lacking. We investigated a priori attitudes of managers and GPs, and their willingness to report in OOHC services. We mapped which methods are used. Methods : A telephone questionnaire was conducted with the managers of all 27 OOHC centers in Flanders. It assessed the design of used reporting systems and the attitudes towards SIR. A paper survey was administered to assess GPs' attitudes in two large out-of-hours primary care centers. Results : All managers participated ( N = 23). Seventy percent used some form of incident reporting system, with a large design variation. All managers thought SIR is important to improve quality and safety. Seven managers predicted that GPs would be hesitant to use SIR. In the GPs' survey (response rate 58%), 69.7% of responders had experienced an incident and 74.5% would tend to report it. 81.1% agreed that an incident has to be analyzed, discussed, and should lead to an improvement plan. The majority believed SIR could create openness about adverse events and would improve job satisfaction. One out of five feared that it would make their job more difficult, and 39% were afraid the report could be used against the reporter. Conclusion : OOHC center managers and GPs show positive attitudes towards SIR. There is a large variation in the currently used methods. Future projects could focus on interventions of implementation of SIR in OOHC.